ANALISIS DAMPAK PENERAPAN ESOP (EMPLOYEE STOCK OWNERSHIP PROGRAM) TERHADAP KINERJA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lilis Susilawaty; Dewi Dewi (Business Management Journal, 2017)
This study aims to determine whether the implementation of the ESOP share program (employee stock ownership program) can be an alternative strategy to minimize conflicts of interest that occur between shareholders and management because these differences in interests can affect the performance of the company. Sampling method used is purposive sampling method. Data analysis technique using Test Signal (Wilcoxon Signed Rank Test) which previously been done Test of Normality using Kolmogorov-Smirnov Test.The results showed that there are differences in sales growth before and after the implementation of ESOP (employee stock ownership program). While there is no difference in return on assets and net profit margin before and after the implementation of ESOP (employee stock ownership program).Keywords:employee stock ownership program, return on assets, net profit margin, sales growth